The Role of Spiritual and Educational Events in the Life of Students - Ibragimova, Gulnora (The Lingua Spectrum, 2025)
This article provides an expanded analysis of the role and significance of spiritual and educational events in students’ lives, examining their influence on intellectual, ethical, and social development. In the context of globalization, strengthening the moral and cultural foundations of the younger generation has become a key priority of Uzbekistan’s state policy. Reforms introduced in recent years, inspired by President Shavkat Mirziyoyev’s principle “Spirituality is the greatest power,” have enabled a systematic integration of spiritual-educational activities into the educational environment. Meetings with scholars and public figures, thematic seminars, cultural programs, and spiritual-educational hours held in schools and universities contribute to the expansion of students’ worldviews, the formation of national pride, and the development of moral consciousness. The study analyzes the diversity of these activities, their pedagogical value, and their role in enhancing students’ social engagement and personal responsibility. Based on observed practices, practical recommendations are proposed to further strengthen the spiritual-educational system in higher education. Overall, the article concludes that such activities play a vital role in shaping well-rounded, morally mature, and socially responsible individuals prepared to actively contribute to society.